Segregation Sensitivity of Concrete—Quantification by Concrete Density - Maureen Denu; Frank Spörel; David Alós Shepherd; Hassan Ahmed; Jouni Punkki; Frank Dehn (Construction Materials, 2025)
Concrete segregation can lead to variations in hardened concrete’s properties, such as strength and Young’s modulus, or permeability, resulting in changing volume ratios between aggregates and paste within a concrete element. One approach to mitigate this potential risk is to conduct a performance test to assess vibrated concrete’s segregation sensitivity. This paper outlines various methods to evaluate the segregation sensitivity of vibrated concrete, aiming to support adequate concrete casting. The focus is on practical feasibility while maintaining test accuracy. For hydraulic engineering in Germany, test procedures to evaluate segregation sensitivity on fresh and hardened concrete based on aggregate distribution are described in the “BAW-Code of practice MESB”. However, this method is very complex and, therefore, difficult to implement in practice. Another procedure for hardened concrete is based on concrete density. In this paper, both methods are compared to investigate if evaluating fresh concrete using a simple density criterion leads to a comparably significant differentiation of vibrated concrete with different segregation sensitivities. The primary emphasis lies in accurately classifying examined concretes in terms of their segregation sensitivity, evaluating the scatter of results, and assessing the practical applicability of these methods. The investigations demonstrate that a density-based method can yield reliable and comparable results to those obtained through the wash-out test according to “BAW-Code of practice MESB”. Additionally, a simpler and faster procedure is achievable with the density approach. Hence, density evaluation offers a practical alternative to the wash-out test.